Features of ecology and distribution Dolichoderus quadripunctatus (Linnaeus, 1771) in Belarus - Sinchuk, Aleh V.; Blinov, Vladimir V. (Experimental Biology and Biotechnology, 2017)
The article deals with the geographical distribution and ecological features of Dolichoderus quadripunctatus (Linnaeus, 1771) in Belarus. This species first was discovered in 1980 in the south of the Pripyat National Park. It was found that the northern boundary of the range of D. quadripunctatus passes over the south and east of Belarus. The northernmost point of registration of D. quadripunctatus (12.08.2015) is in Shklov city park. This dendrobionts forms colonies in a various foliar woody plants: Salix sp., Quercus robur, Carpinus sp., Alnus glutinosa, Acer platanoides, Populus sp., Cornus sp., Juglans regia, Tilia cordata. The oaks are the most preferred for the settlement. The protection of species realizes through the conservation of natural habitats.
Keywords: Dolichoderus quadripunctatus; ants; distribution; Belarus